Global Energy Security under Different Climate Policies, GDP Growth Rates and Fossil Resource Availabilities - Aleh Cherp; Jessica Jewell; Vadim Vinichenko; Nico Bauer; Enrica De Cian (Fondazione Eni Enrico Mattei (FEEM), 2014)
Energy security is one of the main drivers of energy policies. Understanding energy security implications of long-term scenarios is crucial for informed policy making, especially with respect to transformations of energy systems required to stabilize climate change. This paper evaluates the global energy security under several global energy scenarios, modeled in the REMIND and WITCH integrated assessment models. The paper examines the effects of long-term climate policies on energy security under different assumptions about GDP growth and fossil fuel availability. It uses a systematic energy security assessment framework and a set of global and regional indicators for risks associated with energy trade and resilience associated with diversity of energy options. The analysis shows that climate policies significantly reduce the risks and increase the resilience of energy systems in the first half of the century. Climate policies also make energy supply, energy mix, and energy trade less dependent upon assumptions of fossil resource availability and GDP growth, and thus more predictable than in the baseline scenarios.
Keywords: Q4; Q5; Q51; 330; Energy Security; Energy Scenarios; Long-Term Climate Policies; Fossil Resources Assumptions